Dolastane diterpenes from Canistrocarpus cervicornis and their effects in modulation of drug resistance in Staphylococcus aureus. Issue 22 (17th November 2019) - de Figueiredo, Camilla Silva; Menezes Silva, Suellen Maria Pinto de; Abreu, Lucas Silva; da Silva, Evandro Ferreira; da Silva, Marcelo Sobral; Cavalcanti de Miranda, George Emmanuel; Costa, Vicente Carlos de O.; Le Hyaric, Mireille; Siqueira Junior, José Pinto de; Barbosa Filho, José Maria; Tavares, Josean Fechine
Abstract: One new diterpene (4 R, 7 R, 14 S )-4α, 7α-diacetoxy-10-one-14α-hydroxydolasta-1(15), 8-diene (1 ), and five known compounds (4 R, 7 R, 14 S )-4α, 7α-diacetoxy-14α-hydroxydolasta-1(15), 8-diene (2 ), (4 R, 14 S )-4α, 14α-dihydroxydolasta-1(15), 8-diene (3 ), (4 S, 9 R, 14 S )-4α-acetoxy-9β, 14α-dihydroxydolasta-1(15), 7-diene (4 ), 4-acetoxy-14-hydroxydolasta-1(15), 7, 9-triene (5 ) and isolinearol (6 ), were isolated from Canistrocarpus cervicornis . In this study, dolastane diterpenes were isolated from the alga C. cervicornis and evaluated as modifiers of antibiotic activity in Staphylococcus aureus : SA-1199B, which overexpresses the norA gene RN-4220, which encodes for the protein efflux of macrolides (MRSA), and IS-58 which has the gene encoding the protein TetK. The minimum inhibitory concentrations (MICs) for norfloxacin, tetracycline and erythromycin were determined by the microdilution broth nutrient in the absence and presence of diterpenes at a sub-inhibitory concentration (MIC/4). The extracts of C. cervicornis and isolated diterpenes showed no antibacterial activity, but showed modulatory activity, decreasing the MIC of antibiotics by 4–256 fold. The results indicate that seaweed extracts and diterpenes are potential sources of antibiotic adjuvant, acting as potential inhibitors of efflux pump. Abstract :